Potential of satellite‐based land emissivity estimates for the detection of high‐latitude freeze and thaw states. Issue 5 (15th March 2017) - Prakash, Satya; Norouzi, Hamid; Azarderakhsh, Marzi; Blake, Reginald; Khanbilvardi, Reza
Abstract: Reliable detection of freeze and thaw (FT) states is crucial for the terrestrial water cycle, biogeochemical transitions, carbon and methane feedback to the atmosphere, and for the surface energy budget and its associated impacts on the global climate system. This paper is novel in that for the first time a unique approach to examine the potential of passive microwave remotely sensed land emissivity and its added values of being free from the atmospheric effects and being sensitive to surface characteristics is being applied to the detection of FT states for latitudes north of 35°N. Since accurate characterizations of the soil state are highly dependent on land cover types, a novel threshold‐based approach specific to different land cover types is proposed for daily FT detection from the use of 3 years (August 2012 to July 2015) of the Advanced Microwave Scanning Radiometer‐2 land emissivity estimates. Ground‐based soil temperature observations are used as reference to develop threshold values for FT states. Preliminary evaluation of the proposed approach with independent ground observations over Alaska for the year 2015 shows that the use of land emissivity estimates for high‐latitude FT detection is promising. Key Points: Land emissivity shows a potential for detecting freeze and thaw states A threshold method based on estimated emissivity values is suggested for each land cover type Soil temperature is used to derive the algorithm instead of surface air temperature